Aspidistra minor (Asparagaceae, Nolinoideae), a tiny new species from Vietnam - Vislobokov, Nikolay A.; Kuznetsov, Andrey N.; Kuznetsova, Svetlana P.; Romanov, Mikhail S.; Nuraliev, Maxim S. (Phytotaxa, 2019)
Aspidistra minor is described and illustrated as a new species from southern Vietnam (Gia Lai province, Kon Chu Rang Nature Reserve). The new species possesses very small ovate to elliptic leaf blades and very small flowers with stamens inserted at the base of the perigone. In flower structure, the new species resembles A. leucographa and A. elatior but strongly differs in shape of leaf blades and position of stamens.